130 Risk Factors for Post-Vasectomy Semen Analysis Non-Adherence in Home-based and Local Lab-based Testing. Issue 1 (1st April 2022) - Zipkin, J; Lin, B; Patel, D; Welliver, C
ABSTRACT: Introduction: Post-vasectomy semen analysis (PVSA) is the recommended method for confirming sterility after vasectomy. Current literature reports poor PVSA adherence rates. Our institution utilized a home-based PVSA test between 2014 and 2017 to address this issue, but we have since reverted back to lab-based testing. Objective: In this study, we compare PVSA adherence rates in home- and lab-based test settings and describe factors that may influence completion rates in each cohort. Methods: We retrospectively identified adult patients who underwent a vasectomy at our institution. Surgeon X and Surgeon Y performed vasectomies from December 2014 to January 2017, while only Surgeon X performed them from July 2017 to August 2020. From 2014-2017, each patient was offered purchase of a home immunochromatographic PVSA kit (SpermCheck®). From 2017-2020, each patient was offered local lab-based testing. We collected data on PVSA completion status and patient demographics to perform two analyses. One compared patients of Surgeon X from 2014-2017 to patients of Surgeon Y from 2014-2017. Another compared patients of Surgeon X from 2014-2017 to patients of Surgeon X from 2017-2020. Results: We identified 285 patients who underwent a vasectomy from 2014-2017 (Surgeon Y, 149; Surgeon X, 136). Adherence with PVSA was 36%. The completion of PVSA increased by a factor of 1.04 per year of patient age at which vasectomy was performed (95% CI 1.01-1.08). The completion of PVSA decreased by a factor of 0.70 with each child (95% CI 0.56-0.87). Patients treated by Surgeon X were less likely to complete PVSA than Surgeon Y (OR 0.56, 95% CI 0.34-0.92). No significant difference in completion was found between insurance type, body mass index (BMI), or if a post-operative call or unplanned visit occurred. We identified 629 patients who underwent a vasectomy by Surgeon X (home-based PVSA, 136; lab-based PVSA, 472). Adherence with PVSA was 29% for the home cohort and 52% for the lab cohort. Patients in the home-based cohort were less likely to complete PVSA than the lab-based cohort (OR 0.37, 95% CI 0.24-0.56). The completion of PVSA decreased by a factor of 0.95 as BMI increased (95% CI 0.92-0.98). The completion of PVSA decreased by a factor of 0.74 with each child (95% CI 0.64-0.85). Patients with self-pay or private insurance were more likely to complete PVSA than those with public insurance (OR 2.37, 95% CI 1.22-4.60). Black patients were less likely to complete PVSA than white patients (OR 0.24, 95% CI 0.08-0.72). No significant difference in completion was found between age at vasectomy, distance between patient home and office, or if a post-operative call or unplanned visit occurred. Conclusions: Adherence with PVSA testing was low in both test settings, though it was significantly higher in local lab setting. Age at vasectomy, number of children, and surgeon influenced PVSA completion rate in the 2014-2017 cohort. Sperm analysis test setting, BMI, number of children, insurance type, and race influenced PVSA completion rate for Surgeon X's patients in both time periods. These findings may help surgeons identify groups to focus on in future initiatives to improve PVSA adherence rates. Disclosure: No